Biochar as a beneficial soil amendment in sandy soils : a long term field and greenhouse study to improve the mechanistic understanding - Haider, Ghulam; Justus Liebig University Giessen (My University, 2016)
The growing awareness about increaseing human population numbers and demands and the concomitant global climate change is an all-embracing subject for humankind. Therefore, it has triggered significant research efforts to meet food security and enable climate change mitigation. Biochar (BC) production and soil application has been proposed as a potential means to improve soil quality and crop production whilst serving carbon sequestration in the face of global climate change. In particular, crop water and nutrients supply is a limiting factor to crop production, even in temperate regions as climate warms, and as the frequency and severity of drought spells increases. Meanwhile, many BC studies have been conducted under greenhouse and field conditions. However, there is a dearth of investigations of BC effects on a soil-plant-atmosphere continuum, nutrient supplies and crop production under temperate field conditions. Therefore, the major aims of this thesis were to quantify the effects of BC amendment (alone or in combination with humic acid product (HAP)) on (a) soil-plant-water relations, (b) nutrients availability (both, macro- and micronutrients), (c) growth and yield of cereals under drought conditions. Furthermore, to identify the impact of BC addition on mineral nitrogen (nitrate (NO3-) and ammonium (NH4+)) retention and greenhouse gas (GHG) emission were investigated. In order to accomplish these goals, laboratory, greenhouse and field studies were carried out during 2012 to 2015, using two levels of biochar amendment (15 and 30 t ha-1) in combination with two watering treatments (60 and 25 - 30% soil water holding capacity WHC in greenhouse and irrigated versus rainfed under field conditions).The WHC and greenhouse gas (GHG) emissions of BC-amended soil were carried out under controlled conditions. The impact of BC/HAP addition on water and nutrients supply was determined by monitoring the following ecophysiological parameters: water relations (leaf osmotic potential, relative water content, stomatal resistance, and leaf transpiration), leaf photosynthesis (photosystem II photochemistry) and final growth and yield of plants. The results of growth and yield improvement (as observed in the greenhouse) were tested on diverse crops under field conditions for four years. In addition, following the initial observations of greater NO3- retention in BC amended soil under greenhouse study, the type and strength of mineral N retention in soil, fresh and field aged biochar were investigated with different mineral N extraction methods.
Keywords: biochar; nitrogen; field study; drought; cereals; ddc:580